Discovery of nitrogen-responsive microbial indicators as metrics of freshwater ecosystem health - Jonathan Warren; Caitlin de Vries; Laura H. Hunt; Amy C. Thorpe; Susheel Bhanu Busi; Martyn G. Kelly; Dina-Leigh Simons; Joe D. Taylor; Daniel S. Read; Kerry Walsh (Water Research, 2026)

A hypervelocity 38 mm bore two-stage light-gas gun impact facility and integrated diagnostic framework - B. Dias; T.J. Ringrose; O. Nash; J. Read; M.G. Gorman; C. Bradley; G.C. Burdiak; P. Jarvis; J. Shadbolt; J.W. Skidmore; N. Hawker; H.W. Doyle (Next Research, 2026)

River Microbiomes as Sentinels of National‐Scale Freshwater Ecosystems - Amy C. Thorpe; Susheel Bhanu Busi; Jonathan Warren; Lindsay K. Newbold; Joe D. Taylor; Kerry Walsh; Daniel S. Read (Global Change Biology, 2026)
Freshwaters face increasing pressures from chemical, hydrological and climatic changes, yet tools for assessing their condition remain limited. River biofilms, composed of diverse microbial communities, integrate environmental signals over space and time, making them sensitive indicators of river health. Using 16S rRNA gene sequencing of more than 1600 biofilms collected across a national river network, we quantified bacterial diversity and community composition and applied network analysis to identify ecologically cohesive sub‐communities with keystone taxa underpinning community stability. Alkalinity, dissolved oxygen, nitrate‐nitrogen and temperature were among the principal gradients shaping community composition. Threshold indicator analyses identified taxa with breakpoints along these gradients, revealing interpretable ecological thresholds. Our results demonstrate the potential for microbiome‐based monitoring frameworks that could complement existing biotic indices, enabling early detection of ecological changes and supporting the integration of genomic indicators into routine ecosystem assessment. This scalable approach offers a powerful strategy for managing freshwaters under accelerating anthropogenic pressures.

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

Patterns and trends of atmospheric mercury in the GMOS network: Insights based on a decade of measurements - Mariantonia Bencardino; Francesco D’Amore; Hélène Angot; Lorenzo Angiuli; Yann Bertrand; Warren Cairns; María C. Diéguez; Aurélien Dommergue; Ralf Ebinghaus; Giulio Esposito; Kateřina Komínková; Casper Labuschagne; et al. (Environmental Pollution, 2024)

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Do storm overflows influence AMR in the environment and is this relevant to human health? A UK perspective on a global issue - Holly J. Tipper; Isobel C. Stanton; Rachel A. Payne; Daniel S. Read; Andrew C. Singer (Water Research, 2024)

Fate and behaviour of Microplastics (> 25µm) within the water distribution network, from water treatment works to service reservoirs and customer taps - Gbotemi A. Adediran; Ruairidh Cox; Monika D. Jürgens; Elise Morel; Richard Cross; Heather Carter; M. Glória Pereira; Daniel S. Read; Andrew C. Johnson (Water Research, 2024)

The foraging ecology of green turtles (Chelonia mydas) in New Caledonia - Tyffen C. Read; Laurent Wantiez; Florent Keller; Jonathan M. Werry; Jason P. van de Merwe; Justin J. Meager; Olivier Chateau; Richard Farman; Colin J. Limpus (Marine Biology, 2024)
Green sea turtles ( Chelonia mydas ) face many threats from anthropogenic activity and are listed as Endangered on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species. They spend the majority of their lives in coastal foraging areas, and show strong fidelity to narrow foraging ranges. Understanding the foraging ecology of green turtles is therefore important for their management and conservation. Using stable isotopes analysis ( n = 200) and identification of stomach contents ( n = 21), this study investigated the foraging ecology of four distinct green turtle foraging aggregations (Goro, Isle of Pines, Ouen Island and Uo/Mato Islands) within the Grand Lagon Sud. This World Heritage Area located in New Caledonia supports regionally important nesting and foraging green turtle populations. The δ 13 C and δ 15 N values of skin samples ranged from − 19.3 to − 7.3‰ and 2.8–15.9‰, respectively. Metrics of isotopic niche and regression analyses were used to assess the degree of omnivory, trophic diversity and potential ontogenetic diet shifts in the different aggregations of foraging green turtles in this location. Each of the four sites and four age-classes had distinct isotopic niches, with evidence of omnivory and ontogenetic shifts, particular in new recruits and juveniles, and at Goro and Uo/Mato Islands. This was generally supported by the stomach contents analyses of a small number of green turtles opportunistically sampled from traditional ceremonies. This study provides important information on the foraging ecology of green turtles in New Caledonia, supporting management outcomes in this region. This collaboration with the tribes of the Grand Lagon Sud is also the first step towards the integrated management of the resource.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Water-soluble polymers: Emerging contaminants detected, separated and quantified by a novel GPC/MALDI-TOF method - Eve C. Tarring; Isabelle Durance; Michael J. Harbottle; Robert Lucas; Daniel S. Read; Benjamin D. Ward (Environmental Pollution, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Depositional and tectonic influences on preservation of Milankovitch record during long-term global cooling: Middle and Upper Ordovician convergent foreland, eastern USA - J. Fred Read; Michael C. Pope; Maya Elrick; Linda Hinnov; John Repetski; Robert T. Ryder; Douglas G. Patchen; Richard Diecchio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Observed trends in scavenging by common bottlenose dolphins ( Tursiops truncatus truncatus ) in for‐hire fisheries in the eastern U.S. Gulf of Mexico - Corie E. Grewal; Jessica R. Powell; Stacey C. Horstman; Nicholas A. Farmer; Oscar Ayala; Andrew J. Read (Marine Mammal Science, 2023)
Interactions between bottlenose dolphin and recreational rod and reel fisheries are a complex issue for resource managers in the United States, which may impact anglers' catch and lead to dangerous situations for scavenging or depredating dolphins. To examine this issue, we analyzed data collected by observers on for‐hire fishing vessels off the eastern U.S. Gulf Coast from 2009 to 2020. A generalized additive model indicated number of anglers, number of discarded fish, proximity to shore, prior scavenging events, type of released fish, and area fished were all significant predictors of scavenging by dolphins. The Florida panhandle had the highest odds of scavenging, while scavenging in the Big Bend and Tampa Bay has increased through time. The Florida panhandle is a well‐known area for illegal feeding of dolphins, suggesting human behavior may be influencing fisheries interactions. Model outputs indicate that dolphins are primarily cuing on fishing activity rather than number of discards, but are more likely to scavenge discards from the family Lutjanidae (snappers), which comprised 40% of observed discards but 80% of scavenging events. This study highlights factors influencing the frequency of dolphin scavenging events, guiding managers and scientists on additional studies and mitigation measures needed to address this issue.

Hypoxia Interrupts the Secondary Production Service Provided by Oyster Reef Macrofauna in Mississippi Sound, USA - Chet F. Rakocinski; J. Read Hendon; Kathy E. VanderKooy; Jeremy M. Higgs; Virginia R. Schweiss; Scott C. McIntosh; Daneen P. Menke (Estuaries and Coasts, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Initial characterization of a bacterial leaf streak susceptibility gene suggests it encodes a membrane transporter that influences seed nutrition and germination - Nathan J. Scinto-Madonich; Shivranjani Baruah; Sameya Young; Katherine Vignona; Andrew C. Read; Sara C.D. Carpenter; Li Wang; Xinying Shi; Geoffrey Chang; Miguel A. Piñeros; Adam J. Bogdanove (Physiological and Molecular Plant Pathology, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Corrigendum to: Impact of sweetpotato starch structures, thermal properties, and granules sizes on sweetpotato fry textures [Food Hydrocolloids 137 108377] - Matthew C. Allan; Quentin D. Read; Suzanne D. Johanningsmeier (Food Hydrocolloids, 2023)

Impact of sweetpotato starch structures, thermal properties, and granules sizes on sweetpotato fry textures - Matthew C. Allan; Quentin D. Read; Suzanne D. Johanningsmeier (Food Hydrocolloids, 2023)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Indicators of the effects of climate change on freshwater ecosystems - Kevin C. Rose; Britta Bierwagen; Scott D. Bridgham; Daren M. Carlisle; Charles P. Hawkins; N. LeRoy Poff; Jordan S. Read; Jason R. Rohr; Jasmine E. Saros; Craig E. Williamson (Climatic Change, 2023)

Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation - Andrew Chin; Fergus John Molloy; Darren Cameron; Jon C. Day; Jessica Cramp; Karin Leeann Gerhardt; Michelle R. Heupel; Mark Read; Colin A. Simpfendorfer (Conservation Biology, 2023)
Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection , contribution , potential impact , risk , threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation.

Seasonal gain in body condition of foraging humpback whales along the Western Antarctic Peninsula - K. C. Bierlich; Joshua Hewitt; Robert S. Schick; Logan Pallin; Julian Dale; Ari S. Friedlaender; Fredrik Christiansen; Kate R. Sprogis; Allison H. Dawn; Clara N. Bird; Gregory D. Larsen; Ross Nichols; et al. (Frontiers in Marine Science, 2022)
Most baleen whales are capital breeders that use stored energy acquired on foraging grounds to finance the costs of migration and reproduction on breeding grounds. Body condition reflects past foraging success and can act as a proxy for individual fitness. Hence, monitoring the seasonal gain in body condition of baleen whales while on the foraging grounds can inform how marine mammals support the costs of migration, growth, and reproduction, as well as the nutritional health of the overall population. Here, we use photogrammetry from drone-based imagery to examine how the body condition of humpback whales ( Megaptera novaeangliae ) changed over the foraging season (November to June) along the Western Antarctic Peninsula (WAP) from 2017 to 2019. This population (IWC stock G) is recovering from past whaling and is growing rapidly, providing an opportunity to study how whales store energy in a prey-rich environment. We used a body area index (BAI) to estimate changes in body condition and applied a Bayesian approach to incorporate measurement uncertainty associated with different drone types used for data collection. We used biopsy samples to determine sex and pregnancy status, and a length-based maturity classification to assign reproductive classes ( n = 228; calves = 31, juveniles = 82, lactating females = 31, mature males = 12, mature unknown sex = 56, non-pregnant females = 12, pregnant females = 3, pregnant & lactating females = 1). Average BAI increased linearly over the feeding season for each reproductive class. Lactating females had lower BAI compared to other mature whales late in the season, reflecting the high energetic costs of nursing a calf. Mature males and non-pregnant females had the highest BAI values. Calves and juvenile whales exhibited an increase in BAI but not structural size (body length) over the feeding season. The body length of lactating mothers was positively correlated with the body length of their calves, but no relationship was observed between the BAI of mothers and their calves. Our study establishes a baseline for seasonal changes in the body condition for this humpback whale population, which can help monitor future impacts of disturbance and climate change.

Towards mapping biodiversity from above: Can fusing lidar and hyperspectral remote sensing predict taxonomic, functional, and phylogenetic tree diversity in temperate forests? - Aaron G. Kamoske; Kyla M. Dahlin; Quentin D. Read; Sydne Record; Scott C. Stark; Shawn P. Serbin; Phoebe L. Zarnetske (Global Ecology and Biogeography, 2022)
Aim Rapid global change is impacting the diversity of tree species and essential ecosystem functions and services of forests. It is therefore critical to understand and predict how the diversity of tree species is spatially distributed within and among forest biomes. Satellite remote sensing platforms have been used for decades to map forest structure and function but are limited in their capacity to monitor change by their relatively coarse spatial resolution and the complexity of scales at which different dimensions of biodiversity are observed in the field. Recently, airborne remote sensing platforms making use of passive high spectral resolution (i.e., hyperspectral) and active lidar data have been operationalized, providing an opportunity to disentangle how biodiversity patterns vary across space and time from field observations to larger scales. Most studies to date have focused on single sites and/or one sensor type; here we ask how multiple sensor types from the National Ecological Observatory Network’s Airborne Observation Platform (NEON AOP) perform across multiple sites in a single biome at the NEON field plot scale (i.e., 40 m × 40 m). Location Eastern USA. Time period 2017–2018. Taxa studied Trees. Methods With a fusion of hyperspectral and lidar data from the NEON AOP, we assess the ability of high resolution remotely sensed metrics to measure biodiversity variation across eastern US temperate forests. We examine how taxonomic, functional, and phylogenetic measures of alpha diversity vary spatially and assess to what degree remotely sensed metrics correlate with in situ biodiversity metrics. Results Models using estimates of forest function, canopy structure, and topographic diversity performed better than models containing each category alone. Our results show that canopy structural diversity, and not just spectral reflectance, is critical to predicting biodiversity. Main conclusions We found that an approach that jointly leverages spectral properties related to leaf and canopy functional traits and forest health, lidar derived estimates of forest structure, fine‐resolution topographic diversity, and careful consideration of biogeographical differences within and among biomes is needed to accurately map biodiversity variation from above.

Comparing Uncertainty Associated With 1-, 2-, and 3D Aerial Photogrammetry-Based Body Condition Measurements of Baleen Whales - K. C. Bierlich; Joshua Hewitt; Clara N. Bird; Robert S. Schick; Ari Friedlaender; Leigh G. Torres; Julian Dale; Jeremy Goldbogen; Andrew J. Read; John Calambokidis; David W. Johnston (Frontiers in Marine Science, 2021)
Body condition is a crucial and indicative measure of an animal’s fitness, reflecting overall foraging success, habitat quality, and balance between energy intake and energetic investment toward growth, maintenance, and reproduction. Recently, drone-based photogrammetry has provided new opportunities to obtain body condition estimates of baleen whales in one, two or three dimensions (1D, 2D, and 3D, respectively) – a single width, a projected dorsal surface area, or a body volume measure, respectively. However, no study to date has yet compared variation among these methods and described how measurement uncertainty scales across these dimensions. This associated uncertainty may affect inference derived from these measurements, which can lead to misinterpretation of data, and lack of comparison across body condition measurements restricts comparison of results between studies. Here we develop a Bayesian statistical model using known-sized calibration objects to predict the length and width measurements of unknown-sized objects (e.g., a whale). We use the fitted model to predict and compare uncertainty associated with 1D, 2D, and 3D photogrammetry-based body condition measurements of blue, humpback, and Antarctic minke whales – three species of baleen whales with a range of body sizes. The model outputs a posterior predictive distribution of body condition measurements and allows for the construction of highest posterior density intervals to define measurement uncertainty. We find that uncertainty does not scale linearly across multi-dimensional measurements, with 2D and 3D uncertainty increasing by a factor of 1.45 and 1.76 compared to 1D, respectively. Each standardized body condition measurement is highly correlated with one another, yet 2D body area index (BAI) accounts for potential variation along the body for each species and was the most precise body condition metric. We hope this study will serve as a guide to help researchers select the most appropriate body condition measurement for their purposes and allow them to incorporate photogrammetric uncertainty associated with these measurements which, in turn, will facilitate comparison of results across studies.

Assessing the impact of the threatened crucian carp ( Carassius carassius ) on pond invertebrate diversity: A comparison of conventional and molecular tools - Lynsey R. Harper; Lori Lawson Handley; Carl D. Sayer; Daniel S. Read; Marco Benucci; Rosetta C. Blackman; Matthew J. Hill; Bernd Hänfling (Molecular Ecology, 2021)
Fishes stocked for recreation and angling can damage freshwater habitats and negatively impact biodiversity. The pond‐associated crucian carp ( Carassius carassius ) is rare across Europe and is stocked for conservation management in England, but its impacts on pond biota are understudied. Freshwater invertebrates contribute substantially to aquatic biodiversity, encompassing many rare and endemic species, but their small size and high abundance complicate their assessment. Practitioners have employed sweep‐netting and kick‐sampling with microscopy (morphotaxonomy), but specimen size/quality and experience can bias identification. DNA and environmental DNA (eDNA) metabarcoding offer alternative means of invertebrate assessment. We compared invertebrate diversity in ponds ( N = 18) with and without crucian carp using morphotaxonomic identification, DNA metabarcoding and eDNA metabarcoding. Five 2 L water samples and 3 min sweep‐net samples were collected at each pond. Inventories produced by morphotaxonomic identification of netted samples, DNA metabarcoding of bulk tissue samples and eDNA metabarcoding of water samples were compared. Alpha diversity was greatest with DNA or eDNA metabarcoding, depending on whether standard or unbiased methods were considered. DNA metabarcoding reflected morphotaxonomic identification, whereas eDNA metabarcoding produced markedly different communities. These complementary tools should be combined for comprehensive invertebrate assessment. Crucian carp presence minimally reduced alpha diversity in ponds, but positively influenced beta diversity through taxon turnover (i.e., ponds with crucian carp contained different invertebrates to fishless ponds). Crucian carp presence contributes to landscape‐scale invertebrate diversity, supporting continued conservation management in England. Our results show that molecular tools can enhance freshwater invertebrate assessment and facilitate development of more accurate and ecologically effective pond management strategies.

Plant silicon application alters leaf alkaloid concentrations and impacts parasitoids more adversely than their aphid hosts - Casey R. Hall; Rhiannon C. Rowe; Meena Mikhael; Elizabeth Read; Sue E. Hartley; Scott N. Johnson (Oecologia, 2021)

Correction to: Unraveling unique island colonization events in Elachistocleis frogs: phylogeography, cryptic divergence, and taxonomical implications - Michael J. Jowers; Siti N. Othman; Amaël Borzée; Gilson A. Rivas; Santiago Sánchez-Ramírez; Renoir J. Auguste; J. Roger Downie; Morley Read; John C. Murphy (Organisms Diversity & Evolution, 2021)

Unraveling unique island colonization events in Elachistocleis frogs: phylogeography, cryptic divergence, and taxonomical implications - Michael J. Jowers; Siti N. Othman; Amaël Borzée; Gilson A. Rivas; Santiago Sánchez-Ramírez; Renoir J. Auguste; J. Roger Downie; Morley Read; John C. Murphy (Organisms Diversity & Evolution, 2021)

Contrasting community assembly processes structure lotic bacteria metacommunities along the river continuum - Hyun S. Gweon; Michael J. Bowes; Heather L. Moorhouse; Anna E. Oliver; Mark J. Bailey; Michael C. Acreman; Daniel S. Read (Environmental Microbiology, 2021)
Summary The heterogeneous nature of lotic habitats plays an important role in the complex ecological and evolutionary processes that structure the microbial communities within them. Due to such complexity, our understanding of lotic microbial ecology still lacks conceptual frameworks for the ecological processes that shape these communities. We explored how bacterial community composition and underlying ecological assembly processes differ between lotic habitats by examining community composition and inferring community assembly processes across four major habitat types (free‐living, particle‐associated, biofilm on benthic stones and rocks, and sediment). This was conducted at 12 river sites from headwater streams to the main river in the River Thames, UK. Our results indicate that there are distinct differences in the bacterial communities between four major habitat types, with contrasting ecological processes shaping their community assembly processes. While the mobile free‐living and particle‐associated communities were consistently less diverse than the fixed sediment and biofilm communities, the latter two communities displayed higher homogeneity across the sampling sites. This indicates that the relative influence of deterministic environmental filtering is elevated in sediment and biofilm communities compared with free‐living and particle‐associated communities, where stochastic processes play a larger role.

Binocular responsiveness of projection neurons of the praying mantis optic lobe in the frontal visual field - Ronny Rosner; Ghaith Tarawneh; Veronika Lukyanova; Jenny C. A. Read (Journal of Comparative Physiology A, 2020)
Praying mantids are the only insects proven to have stereoscopic vision (stereopsis): the ability to perceive depth from the slightly shifted images seen by the two eyes. Recently, the first neurons likely to be involved in mantis stereopsis were described and a speculative neuronal circuit suggested. Here we further investigate classes of neurons in the lobula complex of the praying mantis brain and their tuning to stereoscopically-defined depth. We used sharp electrode recordings with tracer injections to identify visual projection neurons with input in the optic lobe and output in the central brain. In order to measure binocular response fields of the cells the animals watched a vertical bar stimulus in a 3D insect cinema during recordings. We describe the binocular tuning of 19 neurons projecting from the lobula complex and the medulla to central brain areas. The majority of neurons (12/19) were binocular and had receptive fields for both eyes that overlapped in the frontal region. Thus, these neurons could be involved in mantis stereopsis. We also find that neurons preferring different contrast polarity (bright vs dark) tend to be segregated in the mantis lobula complex, reminiscent of the segregation for small targets and widefield motion in mantids and other insects.

Bioengineering a Future Free of Marine Plastic Waste - Maya U. Sheth; Sarah K. Kwartler; Emma R. Schmaltz; Sarah M. Hoskinson; E. J. Martz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Andrew J. Read; William C. Eward; Jason A. Somarelli (Frontiers in Marine Science, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Persistence through tough times: fixed and shifting refuges in threatened species conservation - April E. Reside; Natalie J. Briscoe; Chris R. Dickman; Aaron C. Greenville; Bronwyn A. Hradsky; Salit Kark; Michael R. Kearney; Alex S. Kutt; Dale G. Nimmo; Chris R. Pavey; John L. Read; Euan G. Ritchie; et al. (Biodiversity and Conservation, 2019)

Detection of herpesvirus capsids in transmission electron microscopy images using transfer learning - K. Shaga Devan; P. Walther; J. von Einem; T. Ropinski; H. A. Kestler; C. Read (Histochemistry and Cell Biology, 2019)

The ability of moderate resolution imaging spectroradiometer land surface temperatures to simulate cold air drainage and microclimates in complex Arctic terrain - Nicholas C. Pepin; Gary Pike; Spencer Read; Ryan Williams (International Journal of Climatology, 2019)
The Arctic has experienced the most rapid warming in the world in recent decades. Complex topography combines with low solar elevation to create distinct microclimates in Arctic regions, and for many applications such as ecological response and cryospheric change it is critical to obtain reliable temperature trends at the local scale. Due to lack of weather stations, satellite land surface temperature (LST) is increasingly important as a proxy for air temperature ( T air ), but how accurately it can represent microclimates is unknown. For the first time, we compare 10 years (2007–2017) of T air recorded over a dense network of 65 sites (~25 km 2 ) around Kevo Subarctic Research Station in Finland with equivalent moderate resolution imaging spectroradiometer (MODIS) LST at 1 km resolution from MOD11A2/MYD11A2 8‐day products. We assess whether LST can pick up the extreme local gradients in air temperature (>20 °C/km) caused by cold air drainage. Although there is a high correspondence between LST and T air anomalies on a synoptic timescale, small‐scale patterns in T air (lapse rates, aspect contrasts) are not picked up by LST. Temperature gradients in T air become positive (temperature inversions) in winter, and at night, but LST gradients show almost the reverse. Aspect contrasts in T air peak in spring and autumn during the day, but LST shows biggest differences in the evening. Land cover has a large influence on LST, tundra heating up/cooling down more than birch or pine forest. The conflation between land cover and elevation means that differential land‐cover response dominates the elevational LST signal. Contrasts between T air and LST cannot be explained by the number of stations measuring T air in a pixel, elevation error, timing differences or the frequency of cloud cover within the 8‐day composite. Important features of the Arctic climate such as microscale cold air drainage are thus potentially obscured by land‐cover effects.

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Quantitative and qualitative assessment of pollen DNA metabarcoding using constructed species mixtures - Karen L. Bell; Kevin S. Burgess; Jamieson C. Botsch; Emily K. Dobbs; Timothy D. Read; Berry J. Brosi (Molecular Ecology, 2019)
Pollen DNA metabarcoding—marker‐based genetic identification of potentially mixed‐species pollen samples—has applications across a variety of fields. While basic species‐level pollen identification using standard DNA barcode markers is established, the extent to which metabarcoding (a) correctly assigns species identities to mixes (qualitative matching) and (b) generates sequence reads proportionally to their relative abundance in a sample (quantitative matching) is unclear, as these have not been assessed relative to known standards. We tested the quantitative and qualitative robustness of metabarcoding in constructed pollen mixtures varying in species richness (1–9 species), taxonomic relatedness (within genera to across class) and rarity (5%–100% of grains), using Illumina MiSeq with the markers rbcL and ITS 2. Qualitatively, species composition determinations were largely correct, but false positives and negatives occurred. False negatives were typically driven by lack of a barcode gap or rarity in a sample. Species richness and taxonomic relatedness, however, did not strongly impact correct determinations. False positives were likely driven by contamination, chimeric sequences and/or misidentification by the bioinformatics pipeline. Quantitatively, the proportion of reads for each species was only weakly correlated with its relative abundance, in contrast to suggestions from some other studies. Quantitative mismatches are not correctable by consistent scaling factors, but instead are context‐dependent on the other species present in a sample. Together, our results show that metabarcoding is largely robust for determining pollen presence/absence but that sequence reads should not be used to infer relative abundance of pollen grains.

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously? - Jeroen P. A. Hoekendijk; Jerome Spitz; Andrew J. Read; Mardik F. Leopold; Michael C. Fontaine (Marine Mammal Science, 2018)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Seasonality of change: Summer warming rates do not fully represent effects of climate change on lake temperatures - Luke A. Winslow; Jordan S. Read; Gretchen J. A. Hansen; Kevin C. Rose; Dale M. Robertson (Limnology and Oceanography, 2017)
Responses in lake temperatures to climate warming have primarily been characterized using seasonal metrics of surface‐water temperatures such as summertime or stratified period average temperatures. However, climate warming may not affect water temperatures equally across seasons or depths. We analyzed a long‐term dataset (1981–2015) of biweekly water temperature data in six temperate lakes in Wisconsin, U.S.A. to understand (1) variability in monthly rates of surface‐ and deep‐water warming, (2) how those rates compared to summertime average trends, and (3) if monthly heterogeneity in water temperature trends can be predicted by heterogeneity in air temperature trends. Monthly surface‐water temperature warming rates varied across the open‐water season, ranging from 0.013 in August to 0.073°C yr −1 in September (standard deviation [SD]: 0.025°C yr −1 ). Deep‐water trends during summer varied less among months (SD: 0.006°C yr −1 ), but varied broadly among lakes (–0.056°C yr −1 to 0.035°C yr −1 , SD: 0.034°C yr −1 ). Trends in monthly surface‐water temperatures were well correlated with air temperature trends, suggesting monthly air temperature trends, for which data exist at broad scales, may be a proxy for seasonal patterns in surface‐water temperature trends during the open water season in lakes similar to those studied here. Seasonally variable warming has broad implications for how ecological processes respond to climate change, because phenological events such as fish spawning and phytoplankton succession respond to specific, seasonal temperature cues.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Environmental DNA metabarcoding of lake fish communities reflects long‐term data from established survey methods - Bernd Hänfling; Lori Lawson Handley; Daniel S. Read; Christoph Hahn; Jianlong Li; Paul Nichols; Rosetta C. Blackman; Anna Oliver; Ian J. Winfield (Molecular Ecology, 2016)
Organisms continuously release DNA into their environments via shed cells, excreta, gametes and decaying material. Analysis of this ‘environmental DNA ’ ( eDNA ) is revolutionizing biodiversity monitoring. eDNA outperforms many established survey methods for targeted detection of single species, but few studies have investigated how well eDNA reflects whole communities of organisms in natural environments. We investigated whether eDNA can recover accurate qualitative and quantitative information about fish communities in large lakes, by comparison to the most comprehensive long‐term gill‐net data set available in the UK . Seventy‐eight 2L water samples were collected along depth profile transects, gill‐net sites and from the shoreline in three large, deep lakes (Windermere, Bassenthwaite Lake and Derwent Water) in the English Lake District. Water samples were assayed by eDNA metabarcoding of the mitochondrial 12S and cytochrome b regions. Fourteen of the 16 species historically recorded in Windermere were detected using eDNA , compared to four species in the most recent gill‐net survey, demonstrating eDNA is extremely sensitive for detecting species. A key question for biodiversity monitoring is whether eDNA can accurately estimate abundance. To test this, we used the number of sequence reads per species and the proportion of sampling sites in which a species was detected with eDNA (i.e. site occupancy) as proxies for abundance. eDNA abundance data consistently correlated with rank abundance estimates from established surveys. These results demonstrate that eDNA metabarcoding can describe fish communities in large lakes, both qualitatively and quantitatively, and has great potential as a complementary tool to established monitoring methods.

The contrast sensitivity function of the praying mantis Sphodromantis lineola - Vivek Nityananda; Ghaith Tarawneh; Lisa Jones; Natalie Busby; William Herbert; Robert Davies; Jenny C. A. Read (Journal of Comparative Physiology A, 2015)

Ecosystem Consequences of Changing Inputs of Terrestrial Dissolved Organic Matter to Lakes: Current Knowledge and Future Challenges - Christopher T. Solomon; Stuart E. Jones; Brian C. Weidel; Ishi Buffam; Megan L. Fork; Jan Karlsson; Søren Larsen; Jay T. Lennon; Jordan S. Read; Steven Sadro; Jasmine E. Saros (Ecosystems, 2015)

Evaluation of wireless sensor networks (WSNs) for remote wetland monitoring: design and initial results - Carl J. Watras; Michael Morrow; Ken Morrison; Sean Scannell; Steve Yaziciaglu; Jordan S. Read; Yu-Hen Hu; Paul C. Hanson; Tim Kratz (Environmental Monitoring and Assessment, 2014)

Detection of hydrodynamic stimuli by the Florida manatee (Trichechus manatus latirostris) - Joseph C. Gaspard; Gordon B. Bauer; Roger L. Reep; Kimberly Dziuk; LaToshia Read; David A. Mann (Journal of Comparative Physiology A, 2013)

Physical responses of small temperate lakes to variation in dissolved organic carbon concentrations - Jordan S. Read; Kevin C. Rose (Limnology and Oceanography, 2013)
We used a mechanistic physical model to examine the effect of variability in dissolved organic carbon (DOC) concentrations on the physical properties of small temperate lakes. The model was validated on eight small (6 × 10 −4 to 3.8 × 10 −2 km 2 ) lakes in Wisconsin and Michigan, with a standard error 2°C colder than the reduced scenario. We found a nonlinear relationship between DOC and temperature, with clearer (lower DOC) simulations being more sensitive to climate variability, suggesting that DOC may act as a buffer against a warming climate. Our model showed that DOC also influenced epilimnetic depths, as nocturnal mixing (related to the vertical partitioning of heat) was more important than wind‐driven mixing. Small lakes are globally important regulators of biogeochemical cycles and are structurally different from larger lakes. Important feedbacks to physical processes must be accounted for when understanding the effects of changing DOC and climate on small lakes.

Centralized mouse repositories - Leah Rae Donahue; Martin Hrabe de Angelis; Michael Hagn; Craig Franklin; K. C. Kent Lloyd; Terry Magnuson; Colin McKerlie; Naomi Nakagata; Yuichi Obata; Stuart Read; Wolfgang Wurst; Andreas Hörlein; et al. (Mammalian Genome, 2012)

Observations of a western North Atlantic right whale ( Eubalaena glacialis ) birth offshore of the protected southeast U.S. critical habitat - H. J. Foley; R. C. Holt; R. E. Hardee; P. B. Nilsson; K. A. Jackson; A. J. Read; D. A. Pabst; W. A. McLellan (Marine Mammal Science, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Helmand River Hydrologic Studies Using ALOS PALSAR InSAR and ENVISAT Altimetry - Zhong Lu; Jin-Woo Kim; Hyongki Lee; C. K. Shum; Jianbin Duan; Motomu Ibaraki; Orhan Akyilmaz; Chung-Hye Read (Marine Geodesy, 2009)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Leptotrichia endocarditis: Report of two cases from the International Collaboration on Endocarditis (ICE) database and review of previous cases - L. B. Caram; J. P. Linefsky; K. M. Read; D. R. Murdoch; T. Lalani; C. W. Woods; L. B. Reller; S. S. Kanj; M. M. Premru; S. Ryan; M. Al-Hegelan; P. Y. Donnio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

INVITED REVIEW: Molecular analysis of predation: a review of best practice for DNA‐based approaches - R. A. KING; D. S. READ; M. TRAUGOTT; W. O. C. SYMONDSON (Molecular Ecology, 2008)
Molecular analysis of predation, through polymerase chain reaction amplification of prey remains within the faeces or digestive systems of predators, is a rapidly growing field, impeded by a lack of readily accessible advice on best practice. Here, we review the techniques used to date and provide guidelines accessible to those new to this field or from a different molecular biology background. Optimization begins with field collection, sample preservation, predator dissection and DNA extraction techniques, all designed to ensure good quality, uncontaminated DNA from semidigested samples. The advantages of nuclear vs. mitochondrial DNA as primer targets are reviewed, along with choice of genes and advice on primer design to maximize specificity and detection periods following ingestion of the prey by the predators. Primer and assay optimization are discussed, including cross‐amplification tests and calibratory feeding experiments. Once primers have been made, the screening of field samples must guard against (through appropriate controls) cross contamination. Multiplex polymerase chain reactions provide a means of screening for many different species simultaneously. We discuss visualization of amplicons on gels, with and without incorporation of fluorescent primers. In more specialized areas, we examine the utility of temperature and denaturing gradient gel electrophoresis to examine responses of predators to prey diversity, and review the potential of quantitative polymerase chain reaction systems to quantify predation. Alternative routes by which prey DNA might get into the guts of a predator (scavenging, secondary predation) are highlighted. We look ahead to new technologies, including microarrays and pyrosequencing, which might one day be applied to this field.

Comparing Effectiveness of Experimental and Implemented Bycatch Reduction Measures: the Ideal and the Real - T. M. COX; R. L. LEWISON; R. ŽYDELIS; L. B. CROWDER; C. SAFINA; A. J. READ (Conservation Biology, 2007)
Fishers, scientists, and resource managers have made substantial progress in reducing bycatch of sea turtles, seabirds, and marine mammals through physical modifications to fishing gear. Many bycatch‐avoidance measures have been developed and tested successfully in controlled experiments, which have led to regulated implementation of modified or new fishing gear. Nevertheless, successful bycatch experiments may not translate to effective mitigation in commercial fisheries because experimental conditions are relaxed in commercial fishing operations. Such a difference between experimental results and real‐world results with fishing fleets may have serious consequences for management and conservation of protected species taken as bycatch. We evaluated preimplementation experimental measures and postimplementation efficacy from primary and gray literature for three case studies: acoustic pingers that warn marine mammals of the presence of gill nets, turtle excluder devices that reduce bycatch of turtles in trawls, and various measures to reduce seabird bycatch in longlines. Three common themes to successful implementation of bycatch reduction measures are long‐standing collaborations among the fishing industry, scientists, and resource managers; pre‐ and postimplementation monitoring; and compliance via enforcement and incentives.

An eddy covariance mesonet to measure the effect of forest age on land–atmosphere exchange - MICHAEL L. GOULDEN; GREGORY C. WINSTON; ANDREW M. S. McMILLAN; MARCY E. LITVAK; EDWARD L. READ; ADRIAN V. ROCHA; J. ROB ELLIOT (Global Change Biology, 2006)
We deployed a mesonet of year‐round eddy covariance towers in boreal forest stands that last burned in ∼1850, ∼1930, 1964, 1981, 1989, 1998, and 2003 to understand how CO 2 exchange and evapotranspiration change during secondary succession. We used MODIS imagery to establish that the tower sites were representative of the patterns of secondary succession in the region, and Landsat images to show that the individual stands have changed over the last 22 years in ways that match the spatially derived trends. The eddy covariance towers were well matched, with similar equipment and programs, which maximized site‐to‐site precision and allowed us to operate the network in an efficient manner. The six oldest sites were fully operational for ∼90% of the growing season and ∼70% of the dormant season from 2001 or 2002 to 2004, with most of the missing data caused by low battery charge or bad signals from the sonic anemometers. The rates of midday growing‐season CO 2 uptake recovered to preburn levels within 4 years of fire. The seasonality of land–atmosphere exchange and growing‐season length changed markedly with stand age. The foliage in the younger stands (1989, 1998, and 2003 burns) was almost entirely deciduous, which resulted in comparatively short growing seasons that lasted ∼65 days. In contrast, the older stands (1850, 1930, 1964, and 1981) were mostly evergreen, which resulted in comparatively long growing seasons that lasted ∼130 days. The eddy covariance mesonet approach we describe could be used within the context of other ecological experimental designs such as controlled manipulations and gradient comparisons.

Molecular detection of predation by soil micro‐arthropods on nematodes - D. S. READ; S. K. SHEPPARD; M. W. BRUFORD; D. M. GLEN; W. O. C. SYMONDSON (Molecular Ecology, 2006)
The relative importance of the factors driving change in the population dynamics of nematodes in the soil is almost completely unknown. Top‐down control by micro‐arthropod predators may have a significant impact on nematode population dynamics. We report experiments showing that mites and Collembola were capable of reducing nematode numbers in the laboratory and were feeding on a targeted nematode species in the field. A PCR‐based approach was developed for the detection of predation on three species of slug‐ and insect‐pathogenic nematodes: Phasmarhabditis hermaphrodita , Heterorhabditis megidis and Steinernema feltiae . The collembolan Folsomia candida and the mesostigmatid mite Stratiolaelaps miles were employed as model predators to calibrate post‐ingestion prey DNA detection times. Fragments of cytochrome oxidase I (COI) mtDNA were sequenced and species‐specific primers were designed, amplifying 154‐, 154‐ and 203‐bp fragments for each of the nematode species. Detection times for nematode DNA within the guts of Collembola were longer than in mites, with half‐lives (50% of samples testing positive) of 08.75 h and 05.03 h, respectively. F. candida significantly reduced numbers of the nematode H. megidis , with rates of predation of ∼0.4 nematode infective juveniles per collembolan per hour over 10 h. Four taxa of field‐caught micro‐arthropod that had been exposed to the nematode P. hermaphrodita for a period of 12 h were analysed and significant numbers of three taxa tested positive. This is the first application of PCR techniques for the study of nematophagy and the first time these techniques have been used to measure predation on nematodes in the field.

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

The costs of intersexuality: a crustacean perspective - A. T. Ford; T. F. Fernandes; P. A. Read; C. D. Robinson; I. M. Davies (Marine Biology, 2004)

A Bayesian model of stereopsis depth and motion direction discrimination - J. C. A. Read (Biological Cybernetics, 2002)

Genetic diversity among Texas bluegrass genotypes (Poa arachnifera Torr.) revealed by AFLP and RAPD markers - K. Renganayaki; J. C. Read; A. K. Fritz (Theoretical and Applied Genetics, 2001)

A milk growth factor extract reduces chemotherapeutic drug toxicity in epithelial cells in vitro - Vicki L. Taylor; Chris Goddard; Leanna C. Read (In Vitro Cellular & Developmental Biology - Animal, 2001)

A MILK GROWTH FACTOR EXTRACT REDUCES CHEMOTHERAPEUTIC DRUG TOXICITY IN EPITHELIAL CELLS IN VITRO - VICKI L. TAYLOR; CHRIS GODDARD; LEANNA C. READ (In Vitro Cellular & Developmental Biology - Animal, 2001)

HABITAT SELECTION OF FORAGING BOTTLENOSE DOLPHINS IN RELATION TO BOAT DENSITY NEAR CLEARWATER, FLORIDA - Mark C. Allen; Andrew J. Read (Marine Mammal Science, 2000)

Characterising sclerophylly: some mechanical properties of leaves from heath and forest - C. Edwards; J. Read; G. Sanson (Oecologia, 2000)

Subcellular distribution of arabinogalactan proteins in pollen grains and tubes as revealed with a monoclonal antibody raised against stylar arabinogalactan proteins - C. Ferguson; A. Bacic; M. A. Anderson; S. M. Read (Protoplasma, 1999)

Location of cellulose and callose in pollen tubes and grains of Nicotiana tabacum - C. Ferguson; T. T. Teeri; M. Siika-aho; S. M. Read; A. Bacic (Planta, 1998)

Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1) - J. H. D. Bassett; A. A. J. Pannett; S. A. Forbes; R. V. Thakker; M. McCarthy; A. P. Read; B. T. Teh; C. Larsson; S. Kytl; J. Leisti; P. Salmela; G. Weber; et al. (Human Genetics, 1997)